FOREIGN ECONOMIC RELATIONS OF THE REGIONS AND WAYS TO INCREASE EXPORTS - Niyozova Umida Tulkin kizi (The Conference Hub, 2025)
The article examines current trends in the development of foreign economic relations between the regions, analyzes the key factors influencing the growth of export potential, and offers practical recommendations for increasing it. Special attention is paid to the diversification of export goods, improvement of logistics infrastructure and attraction of investments to increase the competitiveness of regions in the global market.
Keywords: foreign economic relations, export, regional economy, international trade, investment, competitiveness.